Embankment of the Ljubljanica River at Špica (Ljubljana) and human impact on the environment in late prehistory - Andrič, Maja; Verbič, Tomaž; Lomax, Johanna; Tolar, Tjaša (Arheološki vestnik, 2017)
This paper presents the results of multi-proxy palaeo-ecological research (luminescence and radiocarbon dating, grain size measurement, loss-on-ignition, pollen, microcharcoal and plant macrofossil analysis), with the aim of reconstructing palaeo-environmental conditions and the impact of prehistoric people on the vegetation in Ljubljana (central Slovenia). The results of luminescence dating and pollen analysis suggest that the Late Copper Age (ca. 2500 cal. BC) archaeological settlement at Špica, which is located on the embankment of the Ljubljanica River, was built directly on silty sediment, which was deposited during the Last Glacial Maximum (LGM, ca. 20 ka). Late glacial and early/middle Holocene sediment, which is missing, was presumably removed by fluvial processes. Therefore, only environmental conditions in the late prehistory after ca. 2500 cal. BC were reconstructed. The results of palynological research suggest that mixed forests with beech, fir, oak, and hornbeam were growing near the Špica settlement. Human impact on the environment was moderate, with weak traces of agricultural activities. After the abandonment of the settlement, the traces of human impact on the environment became more apparent, especially in the Iron Age, when the pollen of plants growing on (abandoned) fields and ruderal ground (cereals, goosefoot, mugwort) and grazing indicators (ribwort plantain) increases. Fir, which is sensitive to grazing and fire, declines. A major clearance of beech forest is dated in the Early Roman Age, most probably in mid-1st century BC (ca. 162 cal. BC–AD 52). These changes of vegetation can be associated with prehistoric and Roman archaeological sites of Tribuna and Prule, which is in the vicinity of Špica.